Who will be idol? The importance of social networks for winning on reality shows - Odelia Heizler; Ayal Kimhi (Institute for the Study of Labor (IZA), 2010)
This paper examines, both theoretically and empirically, the effect of social networks and belonging to minority groups (or race) on the probability of winning in reality television shows. We develop a theoretical model that studies viewer behavior by presenting a framework of competition between two contestants from two different groups. The results are examined empirically using unique contestant data from the highly popular reality show A Star Is Born, the Israeli counterpart of American Idol. Our main finding is that social networks and belonging to minority groups play key roles in the contestant's victory, but their effects are nonlinear: the social network effect is U-shaped, whereas that of belonging to a minority group follows an inverted U shape. Beyond the world of reality TV, this paper sheds light on the general behavior of social networks as well.
Keywords: J15; D71; P16; 330; American Idol; social networks; minority groups; contest; voting; Fernsehprogramm; Spiel; Wettbewerb; Soziales Netzwerk; Ethnische Gruppe; Schätzung; Israel